Effect of Ankle Positions on Gluteus Maximus Activation During Squats - Hanchang Lee; Ilyoung Moon; Chunghwi Yi (Physical Therapy Korea)
Background: Lower limb strength is crucial for stability and functional movement, such as walking, running, squatting, and balance, with the gluteus maximus (Gmax) being pivotal. Squat exercises are commonly used to strengthen the Gmax; however, the impact of ankle position on muscle activation during squats is not well understood. Objects: This study examined Gmax and lower limb muscle activation patterns in three ankle positions during squats, aiming to optimize rehabilitation strategies and enhance exercise prescriptions. Methods: Surface electromyography recorded the activation levels of the Gmax, vastus medialis oblique (VMO), vastus lateralis oblique (VLO), and biceps femoris (BF) across three ankle positions: neutral (NEU), dorsiflexion (DF), and plantarflexion (PF). A repeated-measures design was employed, involving 30 healthy adults (26 males and 4 females) aged 18–30 years. Muscle activation patterns were statistically analyzed to identify significant variations across these conditions, with the significance level set at p < 0.05. Results: During squats, DF of the ankle joint significantly increased Gmax activation compared with PF and NEU positions, indicating that an ankle position closer to DF may enhance hip extension. In contrast, PF was associated with heightened activation of the VMO and VLO, suggesting that this position may be beneficial for exercises focusing on knee stability. No significant changes were observed in the BF activation across the ankle positions, indicative of its limited involvement in response to variations in ankle positioning. Conclusion: These results underscore the importance of ankle joint positioning in modulating lower-limb muscle engagement during squatting. Ankle DF may be recommended to maximize Gmax activation, which is beneficial for hip-focused strengthening, whereas PF may supports knee stability by targeting quadriceps activation. This study provides evidence for adjusting ankle positioning during squat exercises to optimize specific rehabilitation and performance outcomes.